2019
DOI: 10.31651/2076-5835-2018-1-2019-2-3-19
|View full text |Cite
|
Sign up to set email alerts
|

The influence of different CO2 levels on hemodynamics: analytical review of literature

Abstract: Проаналізована наукова література, щодо впливу гіпер-і гіпокапнії на центральну та периферичну гемодинаміку людини. Показані зміни опору резистивних судин та швидкості кровотоку при різних рівнях СО 2 в артеріальній крові. Відмічено, що на відміну від прямого судинорозширювального впливу на коронарний кровообіг, гіперкапнія викликає звуження судин у легеневому кровообігу. Також спостерігається реактивність варіабельність серцевого ритму, частоти серцевих скорочень і роботи серця при таких впливах. За сучасними… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…It corresponds with Sara J. D. S. et al In this research with the usage of invasive coronary reactivity testing and chart review, it was revealed that in women anxiety was significantly associated with coronary endothelial dysfunction [17]. Overall, etCO2 in all observed patients is decreased drastically indicating the risk of life-threatening disorders manifestation [9].…”
Section: Rs Globalsupporting
confidence: 70%
See 1 more Smart Citation
“…It corresponds with Sara J. D. S. et al In this research with the usage of invasive coronary reactivity testing and chart review, it was revealed that in women anxiety was significantly associated with coronary endothelial dysfunction [17]. Overall, etCO2 in all observed patients is decreased drastically indicating the risk of life-threatening disorders manifestation [9].…”
Section: Rs Globalsupporting
confidence: 70%
“…In patients with hyperventilation, hypocarbia was registered in two-thirds of patients [7]. The crucial role of CO2 is defined in vascular tone regulation [8], heart contractility [9], and endothelium functioning [10].…”
Section: Introductionmentioning
confidence: 99%